Additional mathematics simulations - Pelangi Multimedia Technologies Sdn. Bhd.; Penerbitan Pelangi Sdn. Bhd. (Selangor: Pelangi Multimedia Technologies Sdn. Bhd.: Penerbitan Pelangi Sdn. Bhd. (distributors), 2008)
In this cd-rom, questions can be generated infinitely by computers, parameters of simulations can be set and its results
PTSL : volume 1 ; volume 2
Keywords: Mathematics -- Study and teaching -- Simulation methods; Mathematics -- Study and teaching (Secondary); Mathematics